The Impact of Farmer’s Participatory Interventions in Improving the Productivity and Income from Cashew in the Indian West Coast - Mangalassery, S.; Muralidhara, B. M.; Nayak, M. G.; Preethi, P.; Adiga, J. D. (Annals of Arid Zone, 2022)
The participatory extension approaches in the dissemination of agro-techniques serve as an important strategy in reaching the technologies to the clients. Farmer’s participatory extension was carried out in cashew plantations in coastal India to demonstrate the usefulness of scientific management practices of nutrient management. The preliminary survey showed that 65% of the farmers did not apply manure and chemical fertilizers. The rest of the selected farmers applied only less than half of the recommended fertilizers, mainly nitrogenous fertilizers or NPK mixture. Only 23% of fields received a minimal quantity of manures. About 12% of fields received the integrated application of manures and fertilizers. Organic carbon status was low to medium in the selected fields and among major nutrients, nitrogen was the most limiting nutrient, followed by potassium. Micronutrient deficiencies of zinc, boron and molybdenum were also observed. The adoption of scientific nutrient management practices along with other agro-techniques for two years found to increase the soil pH. The organic carbon content was improved by 7% and available nitrogen by 9.7%, soil phosphorus and potassium by 6.6 and 15.8% respectively by the adoption of scientific management practices. Among the micronutrients in soil, the copper content was increased by 19%. The adoption of scientific nutrient management practices as per the soil test and leaf nutrient status was beneficial to improve the nutrient uptake by the plants as observed from the increased leaf nutrient status of all essential nutrients. The beneficial effects of the technologies on improving the yield, net returns and the benefit-cost ratio were experienced by the growers.